Immunosenescence Psychosocial and Behavioral Determinants - Bosch, Jos A.; Phillips, Anna C.; Lord, Janet M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This book presents the first multi-disciplinary approach to the understanding of immune aging, or immunosenescence; it combines biological data and clinical observations with psychological, social, and behavioral perspectives and is thus a valuable and timely contribution to the literature in this area.  Contributors, all eminent scholars in their respective fields, review thoroughly the state of the art in research that examines how psychological and behavioral factors influence the rate and extent of immune system aging.
Introduction to Ageing of the Adaptive Immune System -- The chronic stress of caregiving accelerates the natural aging of the immune system -- Stress and ageing: Effects on neutrophil function -- Stress, Aging, and Wound Healing -- Psychoneuromicrobiology: cytomegalovirus infection as a putative link between stress, aging and immunity -- Psychosocial factors and telomere length in peripheral blood -- Stress-related Behavioural Responses, Immunity and Ageing in animal models -- Socio-economic status and immunosenescence -- Exercise and Immunosenescence -- Obesity and Immunosenescence: Psychological, Behavioral, & Biochemical Pathways -- Sleep and immunity in older age -- The role of stress and adrenal hormones in immunosenescence.   .
Keywords: Immunology; Neurosciences; Geriatrics; Behavioral sciences; Immunology; Neurosciences; Geriatrics/Gerontology.; Behavioral Sciences